An investigation into the fraction of particle accelerators among colliding-wind binaries : Towards an extension of the catalogue - De Becker, M. (2017)
Particle-accelerating colliding-wind binaries (PACWBs) are multiple systems made of early-type stars able to accelerate particles up to relativistic velocities. The relativistic particles can interact with different fields (magnetic or radiation) in the colliding-wind region and produce non-thermal emission. In many cases, non-thermal synchrotron radiation might be observable and thus constitute an indicator of the existence of a relativistic particle population in these multiple systems. To date, the catalogue of PACWBs includes about 40 objects spread over many stellar types and evolutionary stages, with no clear trend pointing to privileged subclasses of objects likely to accelerate particles. This paper aims at discussing critically some criteria for selecting new candidates among massive binaries. The subsequent search for non-thermal radiation in these objects is expected to lead to new detections of particle accelerators. On the basis of this discussion, some broad ideas for observation strategies are formulated. At this stage of the investigation of PACWBs, there is no clear reason to consider particle acceleration in massive binaries as an anomaly or even as a rare phenomenon. We therefore consider that several PACWBs will be detected in the forthcoming years, essentially using sensitive radio interferometers which are capable of measuring synchrotron emission from colliding-wind binaries. Prospects for high-energy detections are also briefly addressed.